AN ASSESSMENT OF THE VARIATION IN KAMESIAH CHANNEL DISCHARGES THAT SUPPLY AL-HAMAR MARSH, TO THE FLUCTUATION IN DISCHARGES FROM THE MOD IN SOUTHERN IRAQ - Haleem K. Alewi; Nazar Mohamed (Proceedings on Engineering Sciences)
One of Iraq's principal drainage systems, the Main Outfall Drain serves 1.5 million hectares of agricultural land that stretches from the southern Baghdad city in the middle of Iraq to the northern Al Basrh city. By the end of 2008, the Main Outfall Drain in the Naseriyah region underwent significant design improvements. Because of the decrease in water discharges, it was utilized to irrigate the Al-Hamar wetlands. The goal of the study paper is to determine the number of discharges that enter the Al Kamesiah Canal and to develop rating curves for water levels and discharges for the Kamesiah Canal and Main Outfall Drain (MOD) after and before pipes (which are situated 2310 meters from the south of Al Kamesiah Channel). Using the HEC RAS 5.07 software, the hydraulic model was built in an unstable environment. It was then run in normal and high discharge circumstances for the last three years, 2017–2018–2019. According to the simulation results, under normal circumstances, there is sixty to sixty-five percent of discharges from the Main Outfall Drain enter marshes across the Al Kamesiah Channel; under high discharge conditions, there are fifteen to thirty-five percent and sixty to eighty-five percent, respectively.